Strategy of the Leadership of Tahfizhul Quran in Increasing Memorization Motivation of Students - Muhammad Wahyu Siregar; Jailani Jailani; Abizal Muhammad Yati (Thawalib: Jurnal Kependidikan Islam, 2026)
Pesantren leadership plays a crucial role in the success of Tahfizhul Qur’an education, particularly in shaping students’ motivation to consistently memorize the Qur’an. At the Tahfizhul Qur’an Syuhada Islamic Boarding School, effective leadership practices are considered decisive for the quality and sustainability of the tahfizh program. Although many pesantrens implement leadership grounded in religious values, empirical studies examining how a religious-participatory leadership strategy can enhance students’ motivation in a local context remain limited. This study aims to analyze the pesantren leadership strategies in increasing students’ motivation in the Tahfizhul Qur’an program. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving the pesantren leader, tahfizh supervisors, and students, and analyzed using an interactive data analysis model. The findings indicate that the pesantren leader applies a religious-participatory leadership style that emphasizes exemplary conduct, direct involvement in the tahfizh program, and the internalization of spiritual values. Students’ motivation is enhanced through spiritual encouragement, personal guidance, recognition of memorization achievements, and a structured, consistent tahfizh program. The study concludes that effective pesantren leadership significantly determines students’ motivation, discipline, and responsibility in maintaining Qur’anic memorization. These findings provide practical guidance for developing humanistic, religious, and sustainable tahfizh leadership models in other pesantrens.